Application Model Cooperative Integrated Reading and Composition (CIRC) to Improve Reading Comprehension Skills of Class V Elementary School Student - Sofia Nur Azhari; Isah Cahyani; Putri Kirana (Universitas Sebelas Maret, 2019)
research was motivated by the low skills of students reading comprehension main focus on subjects Indonesian. Students are still not able to control aspects of reading would like to understand the content of reading, determining the main idea or infer the content of reading. The study was conducted in class V SDN Cibukamanah Cibatu District of Purwakarta. There are 28 students involved in the study, which consisted of 13 male students and 15 female students. The method used in this research is the Classroom Action Research (CAR), which consists of four phases: planning, implementation, observation and reflection and is done in two cycles. Data were collected through observation and preliminary tests. Seen from the initial test results showed that the students only scored an average of 59.82 with a percentage of 59.82% are less and does not reach the predetermined value KKM is 63. To overcome these problems, researchers applied learning models Cooperative Integrated Reading Composition (CIRC). The purpose of this study was to determine the activity and student learning outcomes in reading comprehension skills, after applying the model of Cooperative Integrated Reading And Composition.The findings of the research results can be seen from the acquisition percentage mastery learning achievement of students overall from starting the first cycle which scored an average of 70.8 with a percentage of 70.71% in the category quite well. Then increased in the second cycle the average value obtained at 75.89 with the percentage of 75.89% uncategorized well. From these results, it can be concluded that the application of the model Cooperative Integrated Reading And Composition (CIRC) can improve student learning outcomes, especially reading skills of understanding that seen at the end of each lesson the first cycle and the second cycle showed a considerable increase in value and target indicators in addition to improving learning outcomes also increase the activity of students during the learning process in class V SDN Cibukamanah.